The Effect of the Setempo Program on Service Efficiency at the Belitung Regency SAMSAT Office - Octavedha, Alfin Yuan; Venny Resti Fachlovi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of the Samsat Setempo program on the efficiency of tax payment services in Belitung Regency as material for evaluation and development of public service policies. This study uses a quantitative method with an associative approach. The research population includes all motor vehicle taxpayers who use the Samsat Setempo Program services in Belitung Regency. The sample size is 50 respondents. Research data were collected through questionnaires compiled based on the Samsat Setempo Program indicators and service efficiency. The data analysis techniques used included testing the validity and reliability of the instruments, testing classical assumptions, and testing hypotheses with partial significance tests (t-tests). The entire data analysis process was carried out using SPSS software version 27. The results showed that the effect of the Setempo program on service efficiency at the Belitung Regency Samsat office was positive and significant, meaning that the Setempo program could be used as a follow-up strategy in improving regional taxation services in Belitung Regency.